Hercegovina: juče, danas, sutra (Tape 2 of 2)
The program opens with a brief description of Bosnian history. The second segment provides Muslim "green berets" testimonies about where they got their ammunition, and how they raped women and young girls. The third segment is "Crime in Kupres". The fourth "Bosnian in flames" focuses on Sarajevo. A young boy in a hospital recalls how he was blown out of his bed by an explosion. The fifth segment shows countless numbers of men in line, with no shirts and shoes, as they wait to get a bowl of food.